Studies on lung capacity - Normal values ​​in men - Rotta O., Andrés (1936)
50 tests were performed lung capacity and its subdivisions in young male subjects. The method used was the dilution O2 in normal breathing, Christie. Age, weight, height, surface area and physical and radiological characteristics of the thorax have been presented separately and correlated with lung capacity and its subdivisions, following procedures and techniques described. 15 has been verified "respiratory dead space" and 15 measurements of vital capacity in the sitting and supine positions dorsal determinations. The results have been somparados with which encuentrn in the medical literature, reviewing, in each series of measurements, the significance of the differences found. They briefly discussed the differences found among subjects from the height and residents at sea level, proposing a comprehensive study in this regard that an assessment, accurately, the value of these differences.